Işık Kirliliği - Çetegen, Duygu; Batman, Alp (İstanbul Kültür Üniversitesi Yayınları, 2005)
Bu çalışmanın amacı, ışık kirliliği konusunda bilgi vermek, konuya duyarlılığı arttırmak, ülkemizde ışık kirliliği açısından alınması gereken önlemlerden bahsetmek ve bilinçlenmeye katkıda bulunmaktır. Bu yazıda İstanbul’da yapılan gözlemler sunulacaktır, mevcut sorunlar ve alınabilecek önlemler hakkında bilgi verilecektir. Sadece astronomi çalışmalarının devamı için değil, sağlıklı bir çevrede yaşantımıza devam edebilmemiz için ışık kirliliği konusunda çok daha duyarlı olmamız gerekmektedir.

Today it is not possible for people, who live in or near cities, to have a view of the universe. Since the population of the urban areas increased, outdoor illumination has been considered to be necessary which now ends up with the consequences of urban sky glow. The misuse of light dosen’t increase nighttime security. The excess light in the sky cause light pollution and it dosen’t only obstruct the night sky view but also threatens the natüre. Since astronomic studies should be done away from air pollution and urban sky glow resources, the sky glow which illuminates the night sky is a threat to amateur and Professional astronomy. Understanding the concept of light pollution is very important to control it. Some of the precautions to be considered are using night lighting only when it is necessary, directing the light downward in order to prevent illuminating the sky, using low pressure sodium light sources if color rendering index is not very important and avoiding development near existing observatories.
Keywords: Işık Kirliliği; Light Pollution